2013
DOI: 10.1088/1742-6596/474/1/012019
|View full text |Cite
|
Sign up to set email alerts
|

Action-angle variables for spherical mechanics related to near horizon extremal Myers–Perry black hole

Abstract: We provide a systematic account of integrability of the spherical mechanics associated with the near horizon extremal Myers-Perry black hole in arbitrary dimension for the special case that all rotation parameters are equal. The integrability is established both in the original coordinates and in action-angle variables. It is demonstrated that the spherical mechanics associated with the black hole in d = 2n + 1 is maximally superintegrable, while its counterpart related to the black hole in d = 2n lacks for on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…We presented both the Hamiltonians and the integrals of motion as well as performed a reduction to a spherical mechanics which is governed by the Casimir invariant of the conformal group SO(2, 1). These models provide one-parameter deformations of the systems constructed recently in [20,21,22]. It was demonstrated that they are superintegrable but not maximally superintegrable, lacking one integral of motion in the odd-dimensional case and two integrals of motion in the even-dimensional case.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We presented both the Hamiltonians and the integrals of motion as well as performed a reduction to a spherical mechanics which is governed by the Casimir invariant of the conformal group SO(2, 1). These models provide one-parameter deformations of the systems constructed recently in [20,21,22]. It was demonstrated that they are superintegrable but not maximally superintegrable, lacking one integral of motion in the odd-dimensional case and two integrals of motion in the even-dimensional case.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard the Myers-Perry black hole with all rotation parameters being equal to each other is of particular interest because its symmetry is enlarged to the unitary algebra (in direct sum with extra so(2, 1) algebra in the near horizon case) which is the largest finite-dimensional symmetry algebra possible. In particular, this gives a clue to the construction of new maximally superintegrable models in [20,21,22].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…One can construct another solution to Einstein equations in the Near Horizon extremal limit [9][10][11][12] of MP (NHEMP) black hole [13] (see [14][15][16][17][18][19] for recent studies). The extremal limit of the parameters describes a black hole with the biggest allowed angular momentum for a given BH mass.…”
Section: Introductionmentioning
confidence: 99%